Coronary arteritis as a cause of cardiac rhythm disorders - Rymkiewicz, Emilia; Karczewska, Agnieszka; Lis, Beata; Mosiewicz, Barbara; Sołdaj–Bukszyńska, Katarzyna; Ścirka, Natalia; Grzywa-Celińska, Anna; Rękas-Wójcik, Agata; Grochowski, Cezary; Dzida, Grzegorz; et al. (Journal of Education, Health and Sport, 2017)
Abstract Ischemic heart disease is a unit consisting of all heart ischemic states regardless of their pathomechanism. Despite common knowledge about risk factors, it remains the most frequent cause of death in industrialized countries. Aim of this paper is to present a case of 23-year-old patient hospitalized in the Department of Internal Diseases because of sensation of heart palpitation and weakness due to acute coronary syndrome in course of coronary arteritis, which occurred 7 years earlier. After performing 24-hour cardiac rhythm observation using Holter monitor, episodes of atrioventricular block Mobitz II, sinoatrial block and multiple supraventricular and ventricular excitations were found.